Diurnally continuous dynamics of surface urban heat island intensities of local climate zones with spatiotemporally enhanced satellite-derived land surface temperatures. (15th June 2022) - Dong, Pan; Jiang, Sida; Zhan, Wenfeng; Wang, Chunli; Miao, Shiqi; Du, Huilin; Li, Jiufeng; Wang, Shasha; Jiang, Lu
Abstract: Interpretation of diurnally continuous dynamics of surface urban heat island intensities (SUHIIs) of various local climate zones (LCZs) is essential for deepening the understanding of the urban climate. However, an easily applicable method for quantifying diurnally continuous dynamics of LCZ-based SUHIIs is still lacking, and the understanding of the diurnally continuous patterns of LCZ-based SUHIIs remains largely incomplete. To alleviate these gaps, here we developed a simple yet effective method for producing diurnally continuous land surface temperatures (LSTs) of various LCZ types based on an LCZ map and MODIS LSTs. With the proposed method, we further investigated the diurnally continuous dynamics of LCZ-based SUHIIs in Nanjing, China. We obtained the following findings: First, in terms of the annual mean, the diurnal SUHII patterns among various built LCZ types were similar and had a small valley within 0–2 h after sunrise and a peak within 8–12 h after sunrise. Second, the midrise/high-rise built and heavy industry types (i.e., LCZ 4, 5, and 10) exhibited relatively high SUHIIs during a diurnal cycle and the associated daily duration with a significant SUHII (>0.5 K) was greater than 20 h. Third, the diurnal SUHII patterns in summer were analogous to the annual mean patterns for all built LCZ types, yet the patterns of several built LCZ types in winter contrasted significantly the annual mean ones. Our findings are valuable for deepening the understanding of the diurnally continuous dynamics of LCZ-based SUHIIs. Highlights: A method for investigating diurnal dynamics of LCZ-based SUHII was proposed. Diurnal patterns of annual mean SUHII of various built LCZ types were similar. Daily duration with a significant SUHII >20 h occurs for LCZ 4, 5, and 10. Diurnal SUHII patterns of various built LCZ types exhibited large seasonality.